The Awareness and Practice of Breast Self-Examination(Bse) Among Female Polytechnic Students In the Polytechnic, Ibadan (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
This study examined the awareness and practice of Breast Self-Examination (BSE) among female students at The Polytechnic, Ibadan, Nigeria. A total of 423 respondents participated in the study, with a focus on socio-demographic factors, knowledge, attitudes, and behaviors related to breast cancer and BSE. The results indicated that while a significant proportion of respondents were aware of breast cancer and BSE, their knowledge of the correct BSE technique was limited. Despite this awareness, BSE practice was inconsistent, with a notable lack of regularity. Various factors, including age, marital status, religion, ethnicity, level of education, and awareness, were found to influence BSE practice. Attitudinal barriers such as embarrassment, perceived ineffectiveness, and unpleasantness were identified as hindrances to regular BSE. This study highlights the need for improved public health education, particularly targeting young women, to enhance their understanding of breast cancer and promote regular BSE. Health campaigns should emphasize normal and abnormal breast awareness, and healthcare professionals should play a more active role in patient education. Furthermore, involving men in awareness initiatives and fostering collaboration between governments and healthcare practitioners are recommended to establish and maintain effective health promotion programs for younger women, ultimately leading to better breast health awareness and practices.